Pengaruh Online Customer Review terhadap Keputusan Pembelian Online melalui E-Trust pada Produk Viva Cosmetics (Gen Z Kota Bandung): Penelitian - Nida Azizah; Ida Farida Oesman; Ahmad Taufiq Maulana Ramdan; Wildan Guretno Prasetiyo (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This research was conducted to help analye the influence of Online Customer Reviews on Online Purchase Decisions, with E-Trust serving as a mediating variable for Viva Cosmetics products among Gen Z in Bandung City. The research applied such a quantitative method with descriptive and also verificative approach. The data were analyzed using PLS-SEM with the support of SmartPLS software. The technique sampling applied was non-probability sampling by purposive sampling, taking 155 respondents. Primary data were taken by distributing Google Forms questionnaires, while secondary data were gained by literature study. The data analysis stages applied outer model evaluation, inner model, and also test of hypothesis by applying the method of bootstrapping. The analysis reveals that Online Customer Reviews (X) play a significant positive role in shaping Online Purchase Decision (Y) with a T-statistic of 6.371 > 1.96 and also P-value of 0.000 < 0.05. The Online Customer Review variable also has a positive and also significant effect on E-Trust (Z) (t = 10.200; p = 0.000). Furthermore, E-Trust has a positive and also significant effect on Online Purchase Decision with a T-statistic of 4.638 > 1.96 and also P-value of 0.000. The indirect effect test results show that Online Customer Review (X) has an indirect effect on Online Purchase Decision (Y) through E-Trust (Z) with a coefficient value of 0.279, a t-statistic value of 4.175 > 1.96, and also p-value of 0.000 < 0.05. These findings indicate that E-Trust acts as a mediating variable that strengthens the relationship between Online Customer Reviews and also Online Purchase Decisions.